Pengaruh Product Quality dan Experiential Marketing Terhadap Repurchase Intention Pada Produk Skincare Narcisse Beauty Care di Kota Probolinggo - Sindy Aliffiarantika; Abdul Waris (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Product quality is able to influence consumers' perspective on the company. In addition, companies also need to pay attention to the company's image by focusing on the experience obtained by customers. This research intends to find out the impact of product quality and consumer experience on the interest in repurchasing Narcisse Beauty Care skincare porduk. This study is a quantitative research with variables of product quality, experiential marketing, and repurchase intention. Simple random sampling was used as a data collection technique using a questionnaire and as many as 100 people as respondents. The results of this research explain that product quality and experiential marketing have a partial or negative effect on repurchase intention in Narcisse Beauty Care skincare products in Probolinggo City. Narcisse Beauty Care is expected to improve product quality by providing a pleasant smell and making attractive packaging and conducting promotions to attract consumers to repurchase, on the other hand holding discounts to increase repurchase intention.